Cooperative Learning: A Foundation for Project Work - Chau, Meng Huat; Jacobs, George M (Beyond Words, 2021)
This article has one theme and two parts. The theme is that we humans can do more and do it more enjoyably when we cooperate. The first part of the article explains eight principles from cooperative learning, a methodology that facilitates students learning in groups of two-four members, along with the learning they do with teachers and by studying on their own. The second part describes four cooperative learning techniques, as a way to bring to life the eight principles from the first part, and also to provide readers of the article with ready-made ideas for using cooperative learning in their own teaching. This article suggests that shorter cooperative learning activities can prepare students for doing projects, and that students can do shorter cooperative learning activities as part of the work they do on projects.